Assessing Australia's options in the context of Brexit: engaging with the UK and the European Union. Issue 3 (4th May 2018) - Allison-Reumann, Laura; Matera, Margherita; Murray, Philomena
ABSTRACT: The Brexit vote will fundamentally transform the European Union (EU) and will change how the UK relates to Europe and the rest of the world. What are the implications for Australia at this critical juncture? The UK has been a major player in the Australia–EU relationship, and Australia will now need to recalibrate its approach to both the UK and the EU across a range of policy areas. This article examines the future of Australia–UK and Australia–EU relations in the wake of Brexit, and assesses Australia's options going forward. The authors advance three considerations. Firstly, Australia's national interests are best served by adopting a pragmatic rather than nostalgic approach towards future relations with the UK and the EU. Secondly, Australia should avoid pursuing one relationship at the expense of the other and creating a zero-sum dynamic. Finally, Australia's future strategy must consider broader global developments, such as events within its own region and the US presidency.